Phosphorylation at S153 as a Functional Switch of Phosphatidylethanolamine Binding Protein 1 in Cerebral Ischemia-Reperfusion Injury in Rats - Wang, Zhong; Bu, Jiyuan; Yao, Xiyang; Liu, Chenglin; Shen, Haitao; Li, Xiang; Li, Haiying; Chen, Gang (Frontiers in Molecular Neuroscience, 2017)
This study aimed to estimate the role of phosphatidylethanolamine binding protein 1 (PEBP1) in cerebral ischemia-reperfusion (I/R) injury and the underlying mechanisms. Middle cerebral artery occlusion/ reperfusion (MCAO/R) model in adult male Sprague Dawley rats (250-280 g) were established and cultured neurons were exposed to oxygen-glucose deprivation/reoxygenation (OGD/R) to mimic I/R injury in vitro. Expression vectors encoding wild-type PEBP1 and PEBP1 with Ser153Ala mutation (S153A), PEBP1 specific siRNAs, and human recombinant PEBP1 (rhPEBP1) were administered intracerebroventricularly. Endogenous PEBP1 level and its phosphorylation at Ser153 were increased within penumbra tissue and cultured neurons after I/R, accompanied by decreased interaction between PEBP1 and Raf-1. There was a trend toward increased Raf-1/MEK/ERK/NF-κB signaling pathway and phosphatidylcholine-phospholipase C (PC-PLC) activity after I/R, which was enhanced by wild-type PEBP1overexpression and rhPEBP1 treatment and inhibited by PEBP1 (S153A) overexpression. And PEBP1 (S153A) overexpression increased its interaction with Raf-1, reduced infarct size, neuronal death and inflammation, and improved neurological function after I/R, while wild-type PEBP1overexpression exerted opposite effects, suggesting that phosphorylation at Ser153 may exert as a functional switch of PEBP1 by switching PEBP1 from Raf-1 inhibition to PC-PLC activation following I/R. Compared with PEBP1 knockdown, PEBP1 (S153A) overexpression exerted a better rescue effect on I/R injury, which further proved that PEBP1 may be a good protein gone bad with phosphorylation at S153 as a functional switch following I/R. Collectively, our findings suggest that PEBP1 contributed to neuronal death and inflammation after I/R. Selective inhibition of PEBP1 phosphorylation may be a novel approach to ameliorate I/R injury.